1999
DOI: 10.1046/j.1529-8817.1999.3540656.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Effects of Uvb Radiation on Chlorophyll Fluorescence, Biomass, Pigments, and Carbohydrate Fractions in a Benthic Diatom Mat

Abstract: The effects on UVB radiation on a subtidal, cohesive-sediment biofilm dominated by the diatom Gyrosigma balticum (Ehrenberg) Rabenhorst were investigated. Chlorophyll fluorescence parameters (F v /F m , PSII ), pigment concentrations, cell densities, and carbohydrate fractions were measured in four treatments (no UVBR, ambient UVBR, ؉7%, and ؉15% enhancement with UVBR). Enhanced UVBR was provided by a computer-controlled system directly linked to natural diel UVBR levels. Increases in PSII values in the UVBR-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 50 publications
6
65
2
1
Order By: Relevance
“…These findings contrast with prior studies of epipelon, where EPS was occasionally less abundant in +UV treatments (Underwood et al 1999, Roux et al 2002. It is possible that periphytic EPS in our study system was relatively more resistant to UV degradation, or that any UV-induced degradation of EPS was offset by increased periphytic biomass or EPS production.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings contrast with prior studies of epipelon, where EPS was occasionally less abundant in +UV treatments (Underwood et al 1999, Roux et al 2002. It is possible that periphytic EPS in our study system was relatively more resistant to UV degradation, or that any UV-induced degradation of EPS was offset by increased periphytic biomass or EPS production.…”
Section: Resultscontrasting
confidence: 99%
“…To date, most in situ research on this topic has been conducted in marine intertidal epipelon, where the organisms, primarily diatoms, are motile in the sediments and not attached to hard surfaces. Underwood et al (1999) observed a reduction in EPS and concomitant reductions in epipelon biomass and chlorophyll a under an ambient +15% UV-B treatment. In another epipelon study, EPS was reduced in +W plots as compared to -UV plots, but only on a few sample days (Roux et al 2002).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Adaptation processes include protection and repair mechanisms. Avoidance of UV-B includes the ability to move away from the harmful radiation (Underwood et al 1999), and on community level, ''selfshading'' i.e., cells deeper in the assemblages get protection through light absorption by cells at the surface (Blanchard and Gall 1994). In a hard bottom microphytobenthic community the adaptation processes are more important because a movement deeper into the sediment is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems have been designed for terrestrial experiments (Mepsted et al 1996) and have recently been implemented by aquatic ecologists (Underwood et al 1999).…”
Section: Discussionmentioning
confidence: 99%